Theta-regularity and log-canonical threshold - Øygarden, Morten; Tirabassi, Sofia (Mathematica Scandinavica, 2020)
We show that an inequality, proven by Küronya-Pintye, which governs the behavior of the log-canonical threshold of an ideal over $\mathbb {P}^n$ and that of its Castelnuovo-Mumford regularity, can be applied to the setting of principally polarized abelian varieties by substituting the Castelnuovo-Mumford regularity with Θ-regularity of Pareschi-Popa.